2020
DOI: 10.1186/s12931-019-1272-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of the bronchiectasis exacerbation and symptom tool (BEST)

Abstract: Background: Recurrent bronchiectasis exacerbations are related to deterioration of lung function, progression of the disease, impairment of quality of life, and to an increased mortality. Improved detection of exacerbations has been accomplished in chronic obstructive pulmonary disease through the use of patient completed diaries. These tools may enhance exacerbation reporting and identification. The aim of this study was to develop a novel symptom diary for bronchiectasis symptom burden and detection of exace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Another factor that may have contributed to the low self-perception was the daily variability of the symptoms, making it difficult to distinguish symptoms that characterize the occurrence of mild exacerbations. Figure 3 illustrates the fluctuation of symptoms (scores) over time, clearly demonstrating that some patients have symptoms every day (patients 2, 3,4,5,6,7,8,9,10,11,12,14,15,16,22,23,24,25,26,27,28), while others are mostly asymptomatic (patients 5,17,18,19,20,21). Patients who have a productive cough and dyspnea every day will find it more difficult to notice changes in the intensity of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that may have contributed to the low self-perception was the daily variability of the symptoms, making it difficult to distinguish symptoms that characterize the occurrence of mild exacerbations. Figure 3 illustrates the fluctuation of symptoms (scores) over time, clearly demonstrating that some patients have symptoms every day (patients 2, 3,4,5,6,7,8,9,10,11,12,14,15,16,22,23,24,25,26,27,28), while others are mostly asymptomatic (patients 5,17,18,19,20,21). Patients who have a productive cough and dyspnea every day will find it more difficult to notice changes in the intensity of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Artaraz et al . [ 11 ], in a study to develop a symptom diary to detect exacerbation in individuals with bronchiectasis, found that the baseline score, which included cough, dyspnea, fatigue, color of the sputum and fever, had a good correlation with the CAT variables, Leicester questionnaire and SGRQ. These observations allow us to hypothesize that the symptom scores objectively capture the individual’s uniqueness and may eventually be useful for the patient to improve his/her self-perception, thus contributing to the self-management of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A blinded assessor will complete monthly phone calls using questions investigating clinical status in the last month including symptoms, hospital admissions and use of antibiotic therapy (and comparing participant responses to these questions to the international definition of an exacerbation for bronchiectasis [ 7 ]. Participants will also complete the Bronchiectasis Exacerbations and Symptoms Tool (BEST) daily from time of discharge from hospital to six month follow-up [ 51 ]. The BEST tool is a symptom diary, designed to detect bronchiectasis exacerbations, which involves six questions regarding breathlessness, sputum volume, cough, fatigue, sputum colour and cold and flu symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The BEST tool is a symptom diary, designed to detect bronchiectasis exacerbations, which involves six questions regarding breathlessness, sputum volume, cough, fatigue, sputum colour and cold and flu symptoms. It has been shown to be responsive to identifying exacerbations at onset and recovery for individuals with bronchiectasis [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients with bronchiectasis report worse quality of life (QOL) than do persons in the general population [74,75]. Recurrent bronchiectasis exacerbations are related to deterioration of lung function, progression of the disease, impairment of quality of life, and increased rate of mortality [76]. Postoperative QOL and the functional consequences of lung resection (pulmonary function and exercise capacity) are poorly addressed.…”
Section: Quality Of Life (Qol)mentioning
confidence: 99%